Development of Android application : INR App - Pang, Jee Da (2012)
This project is about the development of a healthcare mobile application. The application presented in this project will be on updating patients on their International Normalized Ratio (INR) as well as a few other modules which includes patient’s medication requirements, and also upcoming appointments.